The United Church of Canada a history - Schweitzer, Don 1958- (Wilfrid Laurier Univ. Press, 2012)
"From its inception in the early 1900s, The United Church of Canada set out to become the national church of Canada. This book recounts and analyzes the history of the church of Canada's largest Protestant denomination and its engagement with issues of social and private morality, evangelistic campaigns, and its response to the restructuring of religion in the 1960s